High-barrier transparent polypropylene composite film material and preparation method thereof
By placing the modified polyketone nanofiber film between the polypropylene films, the problem of poor barrier performance of the polypropylene film material is solved through a specific hot pressing process, and a polypropylene composite film material with high barrier, impact resistance and transparency is achieved.
Patent Information
- Application Number
- CN202411721273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The barrier properties of existing polypropylene film materials are poor, making it difficult to effectively isolate substances such as oxygen, carbon dioxide, water vapor and small organic molecules, affecting their performance and life.
Aliphatic polyketone is used as a modified resin film material, combined with polypropylene, and a polyketone nanofiber film is prepared by electrospinning process, and a modified polyketone nanofiber film is placed in the middle of the two layers of polypropylene films. After a strictly limited two-stage hot press forming process, a high-barrier transparent polypropylene composite film material is formed.
It significantly improves the barrier properties and impact resistance of polypropylene composite film materials, while maintaining the transparency of the material, which is suitable for industrial promotion.
Smart Images

Figure CN119502395A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film materials, and in particular relates to a high-barrier transparent polypropylene composite film material and a preparation method thereof. Background Art
[0002] Polypropylene film materials are widely used in many fields such as food, pharmaceutical packaging, agricultural mulch, and building waterproofing due to their excellent mechanical properties, low density, and corrosion resistance, generating huge economic value. However, the barrier properties of existing polypropylene film materials are generally poor, and it is difficult to effectively isolate substances such as oxygen, carbon dioxide, water vapor, and small organic molecules, which has an adverse effect on the performance and life of the protected object.
[0003] At present, there are many methods to improve the barrier properties of polypropylene film materials. First, it can be done by surface coating. This method significantly improves the barrier properties of the material by covering the surface of polypropylene with a layer of high barrier material, such as polyvinylidene chloride, nylon or ethylene-vinyl alcohol copolymer, but the surface coating process is complicated, the cost is high, and its large-scale application is greatly affected; polypropylene film can also be composited with a variety of high barrier resin films such as biaxially oriented polyester film, biaxially oriented nylon film, aluminum-plated film, etc., so as to give the composite film good heat resistance, barrier and strength. This multi-layer composite method also has the problems of complex process and high cost. At the same time, the problems of uneven film thickness, low interface strength, easy stratification, and difficult post-processing are also prominent; secondly, adding nanofillers such as montmorillonite and graphene to the polypropylene matrix to prepare nanocomposites can significantly improve its barrier properties. However, since polypropylene is a non-polar polymer, it has poor compatibility with nanofillers, and the polypropylene molecular chain has a fast crystallization rate and high crystallinity, which makes it easy for nanoparticles to agglomerate and difficult to disperse evenly, greatly weakening the barrier properties of the material. Moreover, this method often leads to a decrease in the transparency of the material, which seriously hinders its application in the packaging field. In addition, polypropylene can also be blended with high-barrier resins such as polyester, polyvinyl alcohol, and nylon to form a film to enhance its barrier properties. This method has a relatively simple process, low cost, and high market acceptance. However, due to the non-polar and easy-to-crystallize properties of polypropylene, and the above-mentioned high-barrier resins are all polar polymers, these high-barrier resins have poor compatibility with polypropylene and are difficult to be evenly distributed in the polypropylene matrix, thus affecting their barrier effect. By adding a compatibilizer, the compatibility of high-barrier resins with polypropylene can be improved to a certain extent to improve its barrier properties, but the process difficulty and production cost will increase accordingly, and the modification effect is limited.
[0004] Therefore, it is of great research significance and application value to develop a transparent polypropylene composite film material which does not require the addition of a compatibilizer, has a simple and easy preparation process, has a low production cost, has good compatibility between a high barrier resin and polypropylene, and has high interlayer interface strength. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, the present invention provides a high-barrier transparent polypropylene composite film material and a preparation method thereof.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] In a first aspect, the present invention provides a method for preparing a high barrier transparent polypropylene composite film material, comprising the following steps:
[0008] a. preparing a polyketone spinning solution and obtaining a polyketone nanofiber membrane by electrospinning;
[0009] b. using N, N'-dicyclohexyl terephthalamide to modify the polyketone nanofiber membrane to obtain a modified polyketone nanofiber membrane;
[0010] c. Divide the polypropylene pellets into two equal parts, place them in the mold frame respectively, and heat press them into two polypropylene films;
[0011] d. Place the modified polyketone nanofiber membrane between two polypropylene films, and then put them into a mold frame together, hot press at 185-195°C for 8-12 min under a pressure of 5-10 MPa, and then cold press at room temperature for 3-10 min under a pressure of 5-10 MPa before taking out; then hot press at 198-202°C for 8-15 min under a pressure of 5-15 MPa, and then cold press at room temperature for 3-10 min under a pressure of 5-15 MPa before taking out to obtain a high barrier transparent polypropylene composite film material.
[0012] In the above preparation method, in step a, hexafluoroisopropanol and dichloromethane are prepared into a mixed solvent in proportion, polyketone and sodium chloride are added in sequence, and after sealing, the mixture is fully stirred at room temperature until the polyketone is completely dissolved, and the polyketone spinning solution is obtained after standing.
[0013] Furthermore, the mass ratio of hexafluoroisopropanol to dichloromethane in the mixed solvent is 1:(0.25-4); the mass ratio of polyketone to the mixed solvent is 1:(10-50); and the mass ratio of polyketone to sodium chloride is 1:(0.005-0.02).
[0014] Furthermore, the polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
[0015] In the above preparation method, in step b, N,N'-dicyclohexylterephthalamide is dissolved in dimethylformamide solution, and then uniformly sprayed on the polyketone nanofiber membrane, and the modified polyketone nanofiber membrane is obtained after standing, drying and cooling.
[0016] Furthermore, the mass ratio of N,N'-dicyclohexylterephthalamide to the polyketone in step a is (0.001-0.005):1; the mass ratio of N,N'-dicyclohexylterephthalamide to dimethylformamide is (0.0002-0.001):1.
[0017] In the above preparation method, in step c, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.1 mm; the mass ratio of the polypropylene pellets to the polyketone in step a is 1:(0.05-0.3).
[0018] Furthermore, the polypropylene pellets are polypropylene resins for film, and have a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
[0019] In the above preparation method, in step d, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene film to the modified polyketone nanofiber membrane is 1:(0.005-0.3).
[0020] In a second aspect, the present invention provides a high barrier transparent polypropylene composite film material prepared by the above preparation method.
[0021] The beneficial effects of the present invention are as follows: the present invention uses aliphatic polyketone as the modified resin film material. The aliphatic polyketone is a ketone-containing olefin-like polymer material, which has the advantages of high barrier, high impact resistance, high temperature resistance, chemical corrosion resistance, wear resistance, etc. It is similar to the molecular chain structure of polypropylene, is transparent itself, and has a refractive index similar to that of polypropylene. When the polyketone film layer and the polypropylene film layer are hot-pressed, they have good interface compatibility and transparency, and are very suitable as the middle layer of a high-barrier transparent polypropylene composite film material. The present invention places a polyketone nanofiber film loaded with N,N'-dicyclohexyl terephthalamide between two layers of polypropylene film. Through a strictly limited two-stage hot-pressing process, the polyketone nanofiber film can form a dense polyketone film, which has excellent barrier properties and can significantly improve the barrier properties of the polypropylene composite film material.
[0022] In addition, the fiber surface of the polyketone nanofiber membrane prepared by the specific electrospinning process of the present invention has a honeycomb structure and a high specific surface area, which is conducive to the efficient loading and uniform dispersion of N, N'-dicyclohexyl terephthalamide on the polyketone membrane. The substance can induce a large amount of polypropylene β crystals under two-stage hot pressing conditions, which not only improves the interface bonding strength between the polyketone layer and the polypropylene matrix, but also further improves the barrier properties and impact toughness of the polypropylene composite film. The raw materials used in this method are cheap and easy to obtain, the molding process is simple and easy, and the production cost is low. While significantly improving the barrier properties of the polypropylene composite film, it also has good impact resistance and transparency, and is suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron micrograph of the polyketone electrospun membrane loaded with N,N'-dicyclohexylterephthalamide in Example 1;
[0024] Figure 2 This is a scanning electron microscope image of the liquid nitrogen brittle fracture cross section of the high barrier transparent polypropylene composite film material in Example 1;
[0025] Figure 3 This is the appearance of the high barrier transparent polypropylene composite film material prepared in Example 1. DETAILED DESCRIPTION
[0026] The technical solution of the present invention can be specifically implemented in the following manner.
[0027] The high-barrier transparent polypropylene composite film material provided by the present invention comprises two layers of polypropylene films and a polyketone film placed between the two layers of polypropylene films, wherein the upper and lower surfaces of the polyketone film are tightly combined with the polypropylene films respectively; the polyketone film is a dense modified polyketone nanofiber film loaded with uniformly dispersed N,N'-dicyclohexyl terephthalamide.
[0028] The present invention provides a method for preparing the above-mentioned high barrier transparent polypropylene composite film material, comprising the following steps:
[0029] (1) preparing a mixed solvent of hexafluoroisopropanol and dichloromethane in a mass ratio of 1:(0.25-4), adding polyketone and sodium chloride in sequence, stirring at room temperature in a sealed state until the polyketone is completely dissolved, and allowing to stand to obtain a polyketone spinning solution;
[0030] Wherein, the mass ratio of polyketone to the mixed solvent is 1:(10-50), and the mass ratio of polyketone to sodium chloride is 1:(0.005-0.02);
[0031] The polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
[0032] (2) spinning the polyketone spinning solution into a film through an electrospinning machine, removing the spun polyketone nanofiber membrane together with the silicone oil paper from the drum after spinning, removing the polyketone nanofiber membrane from the silicone oil paper after standing for 1 to 3 hours, placing it in a plate, transferring it to an oven at 80 to 100° C. and drying it for 12 to 18 hours to obtain a polyketone nanofiber membrane;
[0033] Among them, the specific process of electrospinning is: use the syringe barrel of the electrospinning machine to absorb the polyketone spinning solution, discharge the bubbles inside and install a 20-gauge needle, place it on the booster, and the receiving distance from the syringe needle tip to the roller is 15 cm. Start spinning under the conditions of a translation speed of 100 mm / min, a push speed of 0.5 to 2 mL / h, a positive voltage of 7 kV, a negative voltage of -3 kV, a roller speed of 120 r / min, a temperature of 10 to 50 ° C, and a relative humidity of ≥70%, and stop when the solution in the syringe is consumed.
[0034] (3) dissolving N,N'-dicyclohexylterephthalamide in a dimethylformamide solution at a mass ratio of (0.0002-0.001):1, and then spraying it evenly on the polyketone nanofiber membrane, first placing it at room temperature under ventilation conditions for 24-48 hours, then transferring it to an oven and drying it at 80-120°C for 9-12 hours, and cooling and standing it to obtain a modified polyketone nanofiber membrane;
[0035] Wherein, the mass ratio of N,N'-dicyclohexylterephthalamide to the polyketone in step (1) is (0.001-0.005):1.
[0036] (4) The polypropylene pellets were divided into two equal parts, and were placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.1 mm, respectively, and hot-pressed into two polypropylene films by a flat-plate vulcanizer. The hot-pressing conditions were: hot-pressing temperature of 190° C., hot-pressing time of 10 min, hot-pressing pressure of 10 MPa, and then cold-pressed at room temperature for 5 min under a pressure of 10 MPa before being taken out;
[0037] Wherein, the mass ratio of the polypropylene pellets to the polyketone in step (1) is 1:(0.05-0.3);
[0038] The polypropylene pellets are polypropylene resins for films, with a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
[0039] (5) placing the modified polyketone nanofiber membrane between the two polypropylene films, and then placing them together in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and preparing a polypropylene composite membrane by two-stage hot pressing molding using a flat vulcanizer, wherein the first stage hot pressing conditions are: hot pressing temperature 185-195°C, hot pressing time 8-12 min, hot pressing pressure 5-10 MPa, and then cold pressing at room temperature for 3-10 min under a pressure of 5-10 MPa before taking out; the second stage hot pressing conditions are: hot pressing temperature 198-202°C, hot pressing time 8-15 min, hot pressing pressure 5-15 MPa, and then cold pressing at room temperature for 3-10 min under a pressure of 5-15 MPa;
[0040] Wherein, the mass ratio of the polypropylene membrane to the modified polyketone nanofiber membrane is 1:(0.005-0.3).
[0041] The technical solution and effects of the present invention are further illustrated below through practical examples.
[0042] Example
[0043] 1. Preparation of polypropylene composite film
[0044] 1. Some of the reagents used in the embodiments and comparative examples of the present invention are described as follows:
[0045] Polypropylene 1#: PP, L5D98, Guoneng Baotou Coal Chemical Co., Ltd.;
[0046] Polypropylene 2#: PP, T36F, Sinopec Qilu Petrochemical Company;
[0047] Polypropylene 3#: PP, T98G, PetroChina Dushanzi Petrochemical Company;
[0048] Polyketone 1#: PK, M630A, number average molecular weight 100,000 g / mol, Hyosung Corporation, Korea;
[0049] Polyketone 2#: PK, M930A, number average molecular weight 60,000 g / mol, Hyosung Corporation, Korea;
[0050] N,N'-dicyclohexylterephthalamide: TMB-5, Shanxi Chemical Research Institute (Co., Ltd.);
[0051] Sodium chloride: NaCl, commercially available;
[0052] Hexafluoroisopropanol: HFIP, commercially available;
[0053] Dichloromethane: DCM, commercially available;
[0054] Dimethylformamide: DMF, commercially available.
[0055] 2. Examples 1 to 11
[0056] (1) This embodiment provides a series of high barrier transparent polypropylene composite film materials, the raw material ratios of which are shown in Table 1.
[0057] Table 1 Raw material ratio of Examples 1 to 11 (total weight of polypropylene is 6 g)
[0058]
[0059]
[0060] (2) The polypropylene composite film material in Examples 1 to 11 of the present invention is prepared by the following process:
[0061] 1) After HFIP and DCM are prepared into a mixed solvent in proportion, PK and NaCl are dissolved in the mixed solvent in sequence, and the mixture is fully stirred at room temperature in a sealed state until PK is completely dissolved, and then allowed to stand to obtain an electrospinning solution;
[0062] 2) Use the syringe of the electrospinning machine to absorb the PK spinning solution, discharge the bubbles inside and install a 20-gauge needle, place it on the booster, and the receiving distance from the syringe needle tip to the drum is 15 cm. Start spinning under the conditions of translation speed 100 mm / min, injection speed 1 mL / h, positive voltage 7 kV, negative voltage -3 kV, drum speed 120 r / min, temperature 30 ° C, and relative humidity 80%, and stop when the solution in the syringe is consumed. Remove the spun PK nanofiber membrane from the drum together with the silicone oil paper, place it for 1 hour, remove the PK nanofiber membrane from the silicone oil paper, put it in a plate, and transfer it to an oven to dry at 100 ° C for 12 hours;
[0063] 3) Dissolve TMB-5 in DMF solvent and spray it evenly on the PK nanofiber membrane. Place it at room temperature under ventilation for 24 hours, transfer it to an oven and dry it at 100°C for 12 hours, and then cool and stand to obtain a modified PK nanofiber membrane;
[0064] 4) The PP pellets were divided into two equal parts, and were placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.1 mm, respectively, and hot-pressed into two PP films by a flat vulcanizer. The hot-pressing conditions were: hot-pressing temperature 190°C, hot-pressing time 10 min, hot-pressing pressure 10 MPa, and then cold-pressed at room temperature for 5 min under a pressure of 10 MPa before taking out;
[0065] 5) The modified PK nanofiber membrane was placed between the two PP films, and then placed together in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and a polypropylene composite membrane was prepared by two-stage hot pressing molding using a flat vulcanizer. The first stage of hot pressing conditions were: hot pressing temperature 190°C, hot pressing time 10 min, hot pressing pressure 5 MPa, and then cold pressing at room temperature for 5 min under a pressure of 5 MPa before taking out; the second stage of hot pressing conditions were: hot pressing temperature 200°C, hot pressing time 10 min, hot pressing pressure 10 MPa, and then cold pressing at room temperature for 5 min under a pressure of 10 MPa.
[0066] 3. Comparative Examples 1 to 6
[0067] Comparative Example 1
[0068] 6 g of polypropylene 1# pellets were placed in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and hot-pressed into a film using a flat-bed vulcanizer. The hot-pressing conditions were: hot-pressing temperature 190°C, hot-pressing time 10 min, hot-pressing pressure 10 MPa, and then cold-pressed at room temperature under a pressure of 10 MPa for 5 min before taking out.
[0069] Comparative Example 2
[0070] (1) After 7.2 g HFIP and 4.8 g DCM were prepared into a mixed solvent, 0.6 g polyketone 1#, 6 mg NaCl and 1.5 mg TMB-5 were dissolved in the mixed solvent in sequence, and the mixture was fully stirred at room temperature in a sealed state until PK was completely dissolved, and then cast on a glass plate to form a film. After being placed at room temperature for 12 h, the film was transferred to an oven and dried at 60° C. for 6 h to obtain a modified PK film;
[0071] (2) The remaining steps are the same as steps 4 to 5 of Example 1).
[0072] Comparative Example 3
[0073] (1) After 7.2 g HFIP and 4.8 g DCM are prepared into a mixed solvent, 0.6 g polyketone 1# and 6 mg NaCl are dissolved in the mixed solvent in sequence, and the mixture is stirred at room temperature in a sealed state until PK is completely dissolved, and then cast on a glass plate to form a film. After being placed at room temperature for 12 h, the film is transferred to an oven and dried at 60° C. for 6 h to obtain a PK film;
[0074] (2) Dissolve 1.5 mg TMB-5 in 3 g DMF solution and spray it evenly on the PK film. Place it at room temperature under ventilation for 24 h, transfer it to an oven and dry it at 100 °C for 12 h. Cool it and let it stand to obtain a modified PK film.
[0075] (3) The remaining steps are the same as steps 4 to 5 of Example 1).
[0076] Comparative Example 4
[0077] (1) Same as steps 1 to 4 of Example 1;
[0078] (2) The modified PK nanofiber membrane was placed between the two PP films mentioned above, and then placed together in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm. The polypropylene composite membrane was prepared by a flat-plate vulcanizer through a stage of hot pressing molding. The hot pressing conditions were: hot pressing temperature 200°C, hot pressing time 10 min, hot pressing pressure 10 MPa, and then cold pressing at room temperature for 5 min under a pressure of 10 MPa.
[0079] Comparative Example 5
[0080] (1) Same as steps 1 to 4 of Example 1;
[0081] (2) The modified PK nanofiber membrane was placed between the two PP films, and then placed together in a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm, and a polypropylene composite membrane was prepared by two-stage hot pressing molding using a flat vulcanizer. The first stage of hot pressing conditions were: hot pressing temperature 190°C, hot pressing time 10 min, hot pressing pressure 5 MPa, and then cold pressing at room temperature for 5 min under a pressure of 5 MPa before taking out; the second stage of hot pressing conditions were: hot pressing temperature 190°C, hot pressing time 10 min, hot pressing pressure 10 MPa, and then cold pressing at room temperature for 5 min under a pressure of 10 MPa.
[0082] Comparative Example 6
[0083] (1) Polyketone 2# was used, and the remaining steps were the same as steps 1 to 5 of Example 1).
[0084] 2. Performance testing of polypropylene composite film
[0085] 1. Taking Example 1 as an example, the internal structure and appearance morphology of the high barrier transparent polypropylene composite film material prepared by the method of the present invention were tested. The results are as follows: Figures 1 to 3 shown.
[0086] Figure 1 This is a scanning electron microscope image of the polyketone electrospun membrane loaded with N,N'-dicyclohexyl terephthalamide in Example 1. As can be seen from the figure, the fiber surface of the polyketone electrospun membrane has a uniform honeycomb structure, which is conducive to improving the interface bonding between the polyketone electrospun membrane and the polypropylene matrix, and the particles loaded thereon are N,N'-dicyclohexyl terephthalamide.
[0087] Figure 2 This is a scanning electron microscope image of the liquid nitrogen brittle fracture cross section of the polypropylene composite film in Example 1. As can be seen from the figure, the middle layer is a dense polyketone film, which has good barrier properties and is tightly bonded to the interface between the upper and lower polypropylene layers, which can not only enhance the barrier properties and impact toughness of the composite film material, but also help eliminate the adverse effects of the interface on light transmittance and improve the transparency of the composite film material.
[0088] Figure 3 The appearance of the polypropylene composite film prepared in Example 1. As can be seen from the figure, the polypropylene composite film material has good transparency. The reason is that polypropylene and polyketone are transparent materials themselves, and the molecular structures of the two are similar and the refractive index is close. When the polyketone film is sandwiched between two polypropylene films and hot-pressed into a polypropylene composite film, due to good compatibility and close interface bonding, the adverse effect of the interface on light transmittance is eliminated, so that the prepared polypropylene composite film has high barrier properties and good transparency, which is particularly important for the application of polypropylene materials in the field of packaging.
[0089] 2. The composite membrane was sampled and tested for corresponding performance. The testing methods of the embodiments of the present invention and the comparative examples are as follows:
[0090] Oxygen permeability: Tested according to GB / T 1038-2000 standard, 23°C, 0% RH;
[0091] Water vapor transmission rate: Refer to GB / T 21529-2008 standard test, 38℃, 100%RH;
[0092] Pendulum impact resistance: Tested in accordance with GB / T 8809-2015 standard, 23°C, 50% RH.
[0093] The properties of the polypropylene materials provided in the embodiments and comparative examples were tested according to the aforementioned performance testing method. The results are shown in Table 2.
[0094] Table 2 Performance test results of polypropylene materials provided by Examples 1 to 11 and Comparative Examples 1 to 6
[0095]
[0096] From the above test results, it can be seen that in Examples 1 to 11, the transparent polypropylene composite film material prepared by placing the PK nanofiber film loaded with TMB-5 between two layers of PP film through a strictly limited two-stage hot pressing molding process has excellent barrier properties and impact resistance. Compared with the pure PP film material in Comparative Example 1, the oxygen permeability and water vapor permeability are significantly reduced, and the impact toughness is significantly increased; in Comparative Example 2, TMB-5 is directly added to PK to form a film, and then sandwiched between two layers of PP film for hot pressing molding. Since most of the TMB-5 cannot contact the PP matrix, the amount of polypropylene β crystals generated is very small, the interface bonding force between the PK film and the PP layer is weak, and the barrier properties and impact toughness of the composite film are not good; in Comparative Example 3, TMB-5 is sprayed on the PK cast film, and then the modified PK film is sandwiched between two layers of PP film for hot pressing molding. Since the specific surface area of the PK membrane is too small, it is difficult to firmly load a large amount of TMB-5, resulting in a low amount of polypropylene β crystals generated, and the barrier properties and impact toughness of the composite film are poor; in Comparative Examples 4 and 5, since limited hot pressing conditions were not adopted, a dense PK membrane was not formed in Comparative Example 4, and a large amount of polypropylene β crystals were not induced in Comparative Example 5, so the oxygen permeability and impact toughness were poor; in Comparative Example 6, due to the use of low molecular weight PK, the spinnability was poor, the specific surface area of the PK electrospun membrane was small, and the hot pressing did not form a dense PK membrane, resulting in limited improvement in the barrier properties and impact toughness of the PP composite film.
[0097] From the above, it can be seen that the polypropylene composite film material is obtained by placing the PK nanofiber membrane loaded with TMB-5 between two layers of PP film through a two-stage hot pressing molding process. Under the strictly defined two-stage hot pressing process conditions, the PK nanofiber membrane forms a dense polyketone film, which has good barrier properties and significantly improves the barrier properties of the PP composite film material; at the same time, the fiber surface of the PK electrospinning membrane prepared by a specific electrospinning process has a honeycomb structure and a high specific surface area, which is conducive to the efficient loading and uniform dispersion of TMB-5 on the PK membrane. The large amount of polypropylene β crystals induced by TMB-5 under the above hot pressing conditions not only improve the interface bonding strength between the PK film layer and the PP matrix, but also further improve the barrier properties and impact toughness of the PP composite film, and finally obtain a polypropylene composite film material with excellent barrier properties, impact resistance and transparency.
Claims
1. A method for preparing a high barrier transparent polypropylene composite film material, characterized in that: The steps include: a. preparing a polyketone spinning solution and obtaining a polyketone nanofiber membrane by electrospinning; b. using N, N'-dicyclohexyl terephthalamide to modify the polyketone nanofiber membrane to obtain a modified polyketone nanofiber membrane; c. Divide the polypropylene pellets into two equal parts, place them in the mold frame, and heat press them into two polypropylene films; d. Place the modified polyketone nanofiber membrane between two polypropylene films, and then put them into a mold frame together, hot press at 185-195°C for 8-12 min under a pressure of 5-10 MPa, and then cold press at room temperature for 3-10 min under a pressure of 5-10 MPa before taking out; then hot press at 198-202°C for 8-15 min under a pressure of 5-15 MPa, and then cold press at room temperature for 3-10 min under a pressure of 5-15 MPa before taking out to obtain a high barrier transparent polypropylene composite film material.
2. The method for preparing a high barrier transparent polypropylene composite film material according to claim 1, characterized in that: In step a, hexafluoroisopropanol and dichloromethane are prepared into a mixed solvent in proportion, polyketone and sodium chloride are added in sequence, the mixture is sealed and fully stirred at room temperature until the polyketone is completely dissolved, and the mixture is allowed to stand to obtain a polyketone spinning solution.
3. The method for preparing a high barrier transparent polypropylene composite film material according to claim 2, characterized in that: The mass ratio of hexafluoroisopropanol to dichloromethane in the mixed solvent is 1:(0.25-4); the mass ratio of polyketone to the mixed solvent is 1:(10-50); and the mass ratio of polyketone to sodium chloride is 1:(0.005-0.02).
4. The method for preparing a high barrier transparent polypropylene composite film material according to claim 2, characterized in that: The polyketone is an aliphatic polyketone, which is a linear alternating copolymer synthesized from carbon monoxide, ethylene and propylene, and has a number average molecular weight of 90,000 to 120,000 g / mol.
5. The method for preparing a high barrier transparent polypropylene composite film material according to claim 1, characterized in that: In step b, N,N'-dicyclohexylterephthalamide is dissolved in dimethylformamide solution, and then sprayed uniformly on the polyketone nanofiber membrane, and the modified polyketone nanofiber membrane is obtained after standing, drying and cooling.
6. The method for preparing a high barrier transparent polypropylene composite film material according to claim 5, characterized in that: The mass ratio of N,N'-dicyclohexylterephthalamide to the polyketone in step a is (0.001-0.005):1; the mass ratio of N,N'-dicyclohexylterephthalamide to dimethylformamide is (0.0002-0.001):
1.
7. The method for preparing a high barrier transparent polypropylene composite film material according to claim 1, characterized in that: In step c, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.1 mm; the mass ratio of the polypropylene pellets to the polyketone in step a is 1:(0.05-0.3).
8. The method for preparing a high barrier transparent polypropylene composite film material according to claim 7, characterized in that: The polypropylene pellets are polypropylene resins for films, and have a number average molecular weight of 50,000 to 150,000 g / mol, a melting point of 162 to 168° C., and a melt flow index of 2.8 to 30 g / 10 min (230° C. / 2.16 kg).
9. The method for preparing a high barrier transparent polypropylene composite film material according to claim 1, characterized in that: In step d, the mold frame is a circular mold frame with an inner diameter of 100 mm and a thickness of 0.2 mm; the mass ratio of the polypropylene film to the modified polyketone nanofiber membrane is 1:(0.005-0.3).
10. High barrier transparent polypropylene composite film material, characterized by: The method is prepared according to any one of claims 1 to 9.
